The perfect witness - Siegel, Barry (New York : Ballentine Books, 1999)
Lawyer Greg Monarch has to resort to some dirty tricks to save a former partner accused of murder in California. The partner was framed by nuclear polluters he was exposing. The moral of the story is that sometimes it is necessary to bend the rules to achieve justice.
National College of Business and Arts
Keywords: Examination of witnesses -- Fiction; Detective and mystery fiction